Spectrum of Serum Sodium, Chloride and Potassium and Its Role in the Prediction of Preeclampsia - Khan, Javid Ahmed; Ashraf, Aadil; Qureshi, Waseem A.; Fayaz, Faizana (Achievements and Challenges of Medicine and Medical Science Vol. 9, 2024)
Background and Objective: Preeclampsia is a common complication of pregnancy that leads to maternal and neonatal morbidity and mortality. It may result in lifelong sequelae in pregnant women like reduced life expectancy, increased risks of stroke, cardiovascular disease and diabetes while babies from such mothers have increased risks of preterm birth, perinatal death and neurodevelopmental disability and cardiovascular and metabolic disease later in life. Pre-eclampsia is an intricate multisystem disease, diagnosed by sudden-onset hypertension (>20 weeks of gestation). In spite of decades of research, the aetiology of pre-eclampsia remains poorly defined. To investigate the pathogenesis of pre-eclampsia research is needed to evaluate new prognostic tests and treatments in adequately powered clinical trials. The role of different serum electrolytes in its pathogenesis is in this direction a step as they are considered important for blood pressure regulation. Materials and Methods: A hospital-based cross-sectional study of 100 diagnosed cases of preeclampsia divided into mild and severe according to latest International Society for the Study of Hypertension in Pregnancy ( ISSHP ) guidelines and equal number of age, parity and gestational age-matched women (n=100), that acted as control group, with singleton normal pregnancies, admitted in obstetrics wards from January to March 2022 of our tertiary care hospital associated with GMC Srinagar were included in the study. Clinical examination and laboratory investigations to estimate biochemical parameters were conducted. Data was analyzed with SPSS V:26. Statistical tests to find out the mean standard deviation among the groups and the One-way ANOVA test was applied to find the significance of associations. Results: In the severe preeclampsia group, the mean values of Na+, K+ and Cl- were 134.50±4.24, 4.28±0.74, 106.48±3.41 mEq/L respectively in comparison to the control group 135.57±3.29, 4.12±0.53, 108.20±3.19 mEq/L respectively. Results from one-way ANOVA showed that there was a statistically significant difference between the means of the three groups for systolic blood pressure (SBP), diastolic blood pressure (DBP), Potassium and Chloride levels with p<0.05. A post hoc analysis was used to distinguish the differences in means of these parameters among the groups with p-value <0.05 considered statistically significant. Conclusion: Estimation of readily available serum sodium, chloride and potassium during the course of pregnancy can help to identify preeclampsia and thus reduce the burden of morbidity and mortality in pregnant women and fetal outcome.